Thyroid axis activity and dopamine function in depression. (June 2021) - Duval, Fabrice; Mokrani, Marie-Claude; Erb, Alexis; Danila, Vlad; Lopera, Felix Gonzalez; Foucher, Jack R.; Jeanjean, Ludovic C.
Abstract: Background: Several lines of evidence suggest alterations in both hypothalamic-pituitary-thyroid (HPT) axis and dopamine (DA) function in depressed patients. However, the functional relationships between HPT and DA systems have not been well defined. Methods: We examined thyrotropin (TSH) response to 0800 h and 2300 h protirelin (TRH) challenges, and adrenocorticotropic hormone (ACTH), cortisol and growth hormone (GH) responses to apomorphine (APO, a DA receptor agonist), in 58 drug-free DSM-IV major depressed inpatients without a suicidal behavior, and 22 healthy hospitalized controls. Results: Compared with controls, patients showed 1) lower basal serum 2300 h-TSH, 2300 h-∆TSH, and ∆∆TSH (difference between 2300 h-∆TSH and 0800 h-∆TSH) levels, and 2) lower cortisol response to APO (∆COR). A negative relationship between ∆∆TSH values and hormonal responses to APO was observed in the depressed group, but not in the control group. When patients were classified on the basis of their ∆∆TSH status, patients with reduced ∆∆TSH values (< 2.5 mU/L) showed hormonal APO responses comparable to those of controls. Patients with normal ∆∆TSH values exhibited lower ∆ACTH, ∆COR, and ∆GH values than patients with reduced ∆∆TSH values and controls. Conclusion: Taken together, these results suggest that hypothalamic DA function is unaltered in depressed patients with HPT dysregulation (i.e., increased hypothalamic TRH drive leading to altered TRH receptor chronesthesy on pituitary thyrotrophs). Conversely, hypothalamic DA-receptor function is decreased in patients with normal HPT axis activity. These findings are discussed in the context of the role of TRH as a homeostatic neuromodulator in depression. Highlights: Hypothalamic dopamine function is unaltered in depressed patients with dysregulated thyroid axis activity and vice versa. It is suggested that increased hypothalamic TRH activity can restore or maintain the dopamine system efficiency. Our findings are consistent with the role of TRH as a homeostatic neuromodulator acting on monoaminergic neurotransmission.